Modernity and the western value-action paradox: contributions from conservation psychology - Kyle, Gerard; Landon, Adam (Frontiers in Conservation Science, 2023)
We attempt to bridge the value – action gap inhibiting environmental action by drawing upon work cast within conservation psychology to identify mechanisms by which the processes driving action can be shaped to achieve more sustainable outcomes. The shift toward a more mutualistic orientation with nature suggests the possibility of increasing success of treatments aimed at manipulating the endogenous psychological process (i.e., attitudes, knowledge, efficacy, norms) stemming from value orientation. While empirical evidence illustrates that values can be slow to change, the psychological processes situated higher within the cognitive hierarchy are more susceptible to manipulation. The need for behavioral change is imminent. While developed societies have, for the most part, modernized to the extent basic human needs are amply satisfied, the economic development that has accompanied modernization has coupled economic growth with an unsustainable consumption of natural resources and rising emissions. An increasing number of researchers and activists have called for a transition to a global steady-state economy. We suggest that shifting societal values present an opportunity for modern society to capitalize on humans’ increasing empathy for the natural world and to act in more sustainable ways. Research illustrates that those expressing a stronger affinity toward nature (e.g., mutualists) are more inclined to agree with statements suggesting that environmental protection should be prioritized over economic growth and that climate change is primarily driven by the burning of fossil fuels. Unfortunately, as it presently stands, those most inclined to express this sentiment (i.e., those reporting higher incomes, more years of formal education, and residing in urbanized environments) are also more likely to act in ways that contribute to climate change (e.g., car usage, air travel, household energy use). It is a troubling paradox given they have greater capacity for reducing their ecological footprint. With human values shifting toward a more empathetic orientation toward nature, our review implies that now more than ever, efforts to manipulate elements of the cognitive hierarchy are likely to result in behavioral change that can minimize many anthropogenic drivers of climate change.